18 Colonial Records of the State of Georgia 11 (1910) - (:unkn) unknown (My University, 1755)
"that every person lyable to appear and bear Arms at any Muster, exercise or training hereby appointed pursuant to the Direction of this Act, shall constantly keep in his House, or at his usual place of abode, and bring with him at such muster Exercise or training one Gun or Musquet fit for Service, one Cartridge Box with at least nine Cartridges filled with good Gun powder and Ball that shall fit his Piece"
Keywords: REQUIRED POSSESSION